Harnessing Productive Tensions in Hybrid Organizations: The Case of Work Integration Social Enterprises - Battilana, Julie; Sengul, Metin; Pache, Anne-Claire; Model, Jacob (Academy of Management Journal, 2015)
We examine the factors that influence the social performance of hybrid organizations that pursue a social mission and sustain their operations through commercial activities by studying work integration social enterprises (WISEs). We argue that both social imprinting, defined as a founding team’s early emphasis on accomplishing the organization’s social mission, and economic productivity are important drivers of a WISE’s social performance. However, there is a paradox inherent in the social imprinting of WISEs: Although social imprinting directly enhances a WISE’s social performance, social imprinting also indirectly weakens social performance by negatively affecting economic productivity. Results based on panel data of French WISEs gathered between 2003 and 2007 are congruent with our predictions. To understand how socially imprinted WISEs may mitigate this negative relationship between social imprinting and economic productivity, we also conduct a comparative analysis of case studies. We find that one effective approach is to assign responsibility for social and economic activities to distinct groups while creating “spaces of negotiation”—arenas of interaction that allow members of each group to discuss the trade-offs that they face. We conclude by highlighting the conditions under which spaces of negotiation can effectively be used to maintain a productive tension in hybrid organizations.